Physicochemical and microbiological characteristics of beef offered in the Amazon region - Pinedo, Orlando (2020)
The objective of the research was to evaluate the physicochemical characteristics and microbiology of bovine meat offered in the Amazon region, for which 6 samples with 3 replications were collected in the benefit and 35 samples with 2 replications were commercialized. The description and evaluation of characteristics of each sample was carried out; determining that the meat complies with pH parameters established in NTP 201.055 (5.50 to 6.44), likewise it presents on average 75.53% humidity; 17.79% protein; 17,11% fat; and 5819.28 cal / g of energy; in the beneficiary, 66.67% of the provinces complied with the pH requirements, an average of 83.3% of humidity; 17.79% protein; 4.98% fat and an average of 5812.79 cal / g. The description and microbiological evaluation indicates the presence of enterobacteria in 100% of the samples, a maximum count of 1100 and 860 NMP / g for total and fecal coliforms, respectively; presence of Salmonella Spp in 62% and Shiguella Sp in 39%. Also, in the profit center, a maximum count of 1100 MPN / g for total and fecal coliforms, presence of Salmonella Spp (94%) and Shiguella Sp (28%). However, maximum counts of 65 × 104 CFU / g and 92 × 104 CFU / g were determined for each stage and comply with the standards.